INDONESIA’S TAX LANDSCAPE: UNVEILING CBCR AND TAX HAVENS WITH INSTITUSIONAL OWNERSHIP - Khoirunnisa, Desi Pratiwi Adhila; Abdani, Fadlil (Jurnal Aplikasi Akuntansi, 2024)
This study examines the effects of country-by-country reporting (CbCR) and the utilization of tax havens on tax avoidance strategies while taking into account the moderating effect of institutional ownership. This study employs purposive sampling techniques to evaluate data from 140 businesses listed on the Indonesia Stock Exchange (IDX) in Indonesia from 2013 to 2022. The data analysis is conducted using Eviews 13 software. The research findings suggest that the adoption of CbCR is successful in mitigating tax avoidance strategies. Conversely, tax havens have a negligible effect on tax avoidance. Institutional ownership has the ability to minimize the impact of CbCR by diminishing the correlation between CbCR and tax avoidance. Nevertheless, the presence of institutional ownership does not mitigate the effect of tax havens on the adoption of tax avoidance strategies. This study enhances comprehension regarding the functions of CbCR, tax havens, and institutional ownership in relation to tax avoidance in Indonesia. The practical ramifications of this study include the implementation of CbCR policies to improve corporate transparency and the exploration of various factors that influence tax procedures at the company level in Indonesia.